Clinical utility of metabolic syndrome severity scores: considerations for practitioners - DeBoer MD (Dove Medical Press, 2017)
Mark D DeBoer,1,2 Matthew J Gurka2 11Division of Pediatric Endocrinology, Department of Pediatrics, University of Virginia School of Medicine, Charlottesville, VA, 2Department of Health Outcomes and Policy, College of Medicine, University of Florida, Gainesville, FL, USA Abstract: The metabolic syndrome (MetS) is marked by abnormalities in central obesity, high blood pressure, high triglycerides, low high-density lipoprotein-cholesterol, and high fasting glucose and appears to be produced by underlying processes of inflammation, oxidative stress, and adipocyte dysfunction. MetS has traditionally been classified based on dichotomous criteria that deny that MetS-related risk likely exists as a spectrum. Continuous MetS scores provide a way to track MetS-related risk over time. We generated MetS severity scores that are sex- and race/ethnicity-specific, acknowledging that the way MetS is manifested may be different by sex and racial/ethnic subgroup. These scores are correlated with long-term risk for type 2 diabetes mellitus and cardiovascular disease. Clinical use of scores like these provide a potential opportunity to identify patients at highest risk, motivate patients toward lifestyle change, and follow treatment progress over time. Keywords: metabolic syndrome, insulin resistance, cardiovascular disease, type 2 diabetes, risk prediction